COMBINING ABILITY OF BEAN GENOTYPES ESTIMATED BY LINE × TESTER ANALYSIS UNDER HIGHLY-CALCAREOUS SOILS - E. Ceyhan; A. Kahraman; M. A. Avcı; H. Dalgıç (Journal of Animal and Plant Sciences, 2014)
Line × Tester analysis involving six lines (local populations viz., PV1, PV2, PV3, PV4, PV5 and PV6) and three testers (cultivars viz., Şehirali 90, Akman 98 and Yunus 90) of dry bean (Phaseolus vulgaris L.) was conducted to determine combining ability of seed yield and its related traits under highly calcareous soils. Significant differences of linextester interaction was observed for all characters under the study indicating the prevalence of non-additive variance. Similarly, less than one value of σ2gca / σ2sca ratio for all traits indicated predominance of non-additive gene effects. Significant general and specific combining ability (GCA and SCA) effects were also noted in all the traits. Among the parents, PV5 (Line) and Akman 98 (Tester) were found to be good general combiners for seed yield and yield components. The most promising specific combinations for yield and other traits were PV3 ×Akman 98, PV2xYunus 90, PV6xŞehirali 90 and PV5xYunus 90. These crosses had significant estimates of SCA effects suggesting predominance of non-additive gene action for these traits under highly-calcareous soils. The average heterosis was 53.61 % for seed yield. This study has shown that in order to improve seed yield and yield components in dry bean under highly calcareous soils, the selection of parents should be based on per se performance as well as combining ability.
Keywords: Bean; seed yield; general and specific combining ability